Emulsified asphalt modified high-strength heat-insulation geopolymer foam concrete and preparation method thereof

By using emulsified asphalt modified foam agent in ground polymer foam concrete, the problem of poor dispersion of emulsified asphalt in cement slurry is solved, and the strength and thermal insulation performance of foam concrete are significantly improved, achieving low cost and high performance building materials.

CN119461957AActive Publication Date: 2025-02-18WUHAN UNIV OF TECH
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411413092.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-02-18
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

Among the existing poly foam concrete, the dispersion and compatibility of emulsified asphalt are poor, which limits its enhancement effect on the properties of foam concrete.

Method used

Emulsified asphalt modified foam agent is used as the pore-forming agent, and the emulsified asphalt is uniformly distributed in the pore structure of the foam concrete through the stirring and forming process with the earth polymer slurry.

Benefits of technology

It significantly improves the strength, waterproofing and thermal insulation properties of ground polymer foam concrete, and is simple in process and low in cost, making it suitable for engineering applications.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses emulsified asphalt modified high-strength heat-insulation geopolymer foam concrete and a preparation method thereof. The emulsified asphalt modified high-strength heat-insulating geopolymer foam concrete is prepared by mixing foam prepared from an emulsified asphalt modified foaming agent into geopolymer slurry, stirring, forming, curing and curing, the geopolymer slurry is prepared from the following components in parts by weight: 100 to 300 parts of slag powder, 100 to 200 parts of steel slag powder, 100 to 200 parts of fly ash, 100 to 150 parts of sodium silicate solution, 100 to 150 parts of sodium hydroxide solution and 200 to 400 parts of water; the emulsified asphalt modified foaming agent is prepared from the following components in parts by weight: 0.2 to 0.3 part of foaming agent, 10 to 15 parts of water and 0.8 to 2.7 parts of cationic emulsified asphalt. The foam concrete disclosed by the invention has the characteristics of low cost, no cement, low settling rate, high strength, good heat insulation performance and the like, and the problem of high carbon emission of cement-based foam concrete is relieved by utilizing a large amount of solid waste materials such as the steel slag and the mineral slag.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to an emulsified asphalt modified high-strength heat-insulating geopolymer foam concrete and a preparation method thereof. Background Art

[0002] Geopolymer foam concrete is a porous material prepared by introducing foam into geopolymer slurry by physical or chemical methods. It has the advantages of light weight, heat insulation, noise reduction, etc., and can be used in various non-load-bearing building structures, such as building insulation layer, road base, bridge deck filling layer, etc. Geopolymer, as the main raw material for preparing geopolymer foam concrete, is a silicate material with a three-dimensional network structure, which is synthesized by precursors and alkali activators. Compared with cement, the production process of geopolymer does not require calcination, and a wide variety of industrial solid waste can be selected as precursors. Therefore, geopolymer foam concrete can reduce the dependence of traditional foam concrete on cement, thereby reducing the large amount of carbon dioxide emissions generated by cement.

[0003] As a lightweight concrete material, the compressive strength, waterproof performance and thermal insulation performance of geopolymer foam concrete are crucial for its practical application. The Chinese invention patent with announcement number CN117585949 A discloses a lightweight aggregate geopolymer foam concrete and a preparation method thereof, which uses fly ash and mineral powder as precursors and polystyrene foam as lightweight aggregate to prepare geopolymer foam concrete. The material has the characteristics of low cost, low density and high strength. The Chinese invention patent with announcement number CN109761643 B discloses a method for preparing an ultra-light foam concrete waterproof coating, which uses a polymer coating such as polyacrylamide to significantly improve the mechanical properties and waterproof performance of the foam concrete. However, the raw materials such as polystyrene foam and polymer coating used in the above method are relatively expensive, and the preparation process is relatively complicated, making it difficult to apply in engineering.

[0004] As a common binder for thermal insulation materials, emulsified asphalt has good thermal insulation and bonding properties, which are conducive to enhancing the strength and thermal insulation performance of geopolymer foam concrete. In fact, emulsified asphalt has been widely used in building materials. The Chinese invention patent with announcement number CN116514489 A discloses a new type of cement emulsified asphalt mortar and a preparation method thereof, which uses emulsified asphalt as a modifier to prepare cement emulsified asphalt mortar, and the addition of emulsified asphalt significantly improves the fatigue life of the mortar material. The Chinese invention patent with announcement number CN201510590525.X discloses an emulsified asphalt cement stabilized macadam, which uses emulsified asphalt and cement as binders to prepare a stable macadam base material with excellent low temperature performance and anti-shrinkage performance. However, due to the poor dispersibility and compatibility of emulsified asphalt in cement slurry, the emulsified asphalt in the foam concrete slurry cannot be evenly distributed in the pore structure, thereby limiting the enhancement effect of emulsified asphalt on the performance of foam concrete. Therefore, by developing scientific production methods, emulsified asphalt can be more evenly distributed in geopolymer foam concrete, which can more effectively improve the strength, waterproofness and thermal insulation properties of geopolymer foam concrete while keeping the cost relatively low, which is of great significance for the actual engineering application of geopolymer foam concrete. Summary of the invention

[0005] In view of this, the present invention aims to provide an emulsified asphalt modified high-strength thermal insulating geopolymer foam concrete, which makes extensive use of solid waste materials such as steel slag, thereby alleviating the problem of high carbon emissions of cement-based foam concrete. In addition, the present invention adopts an emulsified asphalt modified foaming agent as a pore-forming agent for foam concrete, which effectively solves the problem of poor compatibility between emulsified asphalt and cement slurry, thereby causing poor performance enhancement effect on foam concrete. The combined effect of the above makes the obtained foam concrete have the characteristics of simple preparation, low cost, no cement, low sedimentation rate, high strength, good thermal insulation performance, etc.

[0006] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0007] An emulsified asphalt modified high-strength thermal insulation geopolymer foam concrete, characterized in that the foam prepared by the emulsified asphalt modified foaming agent is mixed into the geopolymer slurry, and is obtained by stirring, forming, curing and solidification; the geopolymer slurry comprises the following components in parts by weight: 100-300 parts of slag powder, 100-200 parts of steel slag powder, 100-200 parts of fly ash, 100-150 parts of sodium silicate solution, 100-150 parts of sodium hydroxide solution, and 200-400 parts of water; the emulsified asphalt modified foaming agent comprises the following components in parts by weight: 0.2-0.3 parts of foaming agent, 10-15 parts of water, and 0.8-2.7 parts of cationic emulsified asphalt.

[0008] Optionally, the emulsified asphalt modified foamer further comprises 0.6-1 parts of a foam stabilizer by weight.

[0009] Optionally, the foam stabilizer is one or more of hydroxypropyl methylcellulose, polymethacrylamide, and carbon nanotubes, measured by weight.

[0010] Optionally, the fineness of the slag powder, the steel slag powder and the fly ash are all greater than 400 mesh.

[0011] Optionally, the asphalt content in the cationic emulsified asphalt is 50%-60%, and the demulsification time is greater than 4 hours; the foaming agent is one or more of sodium dodecyl sulfate, sodium methyl methacrylate sulfonate, and polymethacrylic acid.

[0012] Optionally, the initial modulus of the sodium silicate solution is 3.3-3.5, the mass ratio of SiO2 to Na2O is 3.25-3.35, and the solid content is greater than 30%.

[0013] Optionally, the sodium hydroxide solution is a solution with a concentration of 12-14 M prepared by dissolving sodium hydroxide particles with a purity greater than 99% in water.

[0014] The second object of the present invention is to provide a method for preparing the above-mentioned emulsified asphalt modified high-strength thermal insulation geopolymer foam concrete, the preparation method comprising the following steps:

[0015] 1) stirring and mixing the sodium silicate solution and the sodium hydroxide solution uniformly, and then leaving the mixture at room temperature for 24 hours to obtain a solution A;

[0016] 2) stirring and mixing the slag powder, the steel slag powder and the fly ash to obtain a mixture B;

[0017] 3) pouring the solution A and 200-400 parts of the water into the mixture B, stirring and mixing evenly to obtain a geopolymer slurry;

[0018] 4) stirring and mixing the foaming agent, the cationic emulsified asphalt and 10-15 parts of the water to obtain an emulsified asphalt modified foaming agent;

[0019] 5) injecting compressed air into the emulsified asphalt modified foaming agent to mix and generate foam, then adding the foam into the geopolymer slurry and stirring and mixing to obtain slurry C;

[0020] 6) The slurry C is poured into a mold for curing and solidification to obtain emulsified asphalt modified high-strength thermal insulation geopolymer foam concrete.

[0021] Optionally, the stirring time in step 1) is not less than 1 hour; the stirring time in step 2) is not less than 2 minutes; the stirring time in step 3) is not less than 2 minutes; the stirring time in step 4) is not less than 1 hour.

[0022] Optionally, the stirring speed in step 5) is 50-60 rpm, and the stirring time is 2-3 min.

[0023] Compared with the prior art, the emulsified asphalt modified high-strength thermal insulation geopolymer foam concrete of the present invention has the following advantages:

[0024] 1. The present invention uses solid wastes such as steel slag powder, slag powder and fly ash as substitute materials, avoiding the use of cement and greatly promoting the effective utilization of waste. This method effectively reduces energy consumption and carbon dioxide emissions, thereby reducing environmental pollution and production costs. This innovative method provides a new way to produce environmentally friendly foam concrete, while achieving significant economic and environmental benefits.

[0025] 2. The present invention selects to mix emulsified asphalt with a foaming agent to prepare an emulsified asphalt modified foamer, and then mixes the modified foam prepared by the emulsified asphalt modified foamer with the geopolymer slurry, rather than directly adding the emulsified asphalt into the geopolymer slurry and then mixing it with the foam. In this way, the emulsified asphalt can be dispersed in the foam and evenly dispersed in the overall pore structure of the foamed concrete along with the foam, which can effectively solve the problem of poor dispersibility of emulsified asphalt in the geopolymer slurry, thereby significantly improving the thermal insulation performance of the obtained foamed concrete.

[0026] 3. The present invention uses emulsified asphalt to prepare modified foam, which can improve the stability and uniformity of the foam, making it more elastic and strong, thereby ensuring better dispersibility while better controlling the pore structure of the foam, thereby improving the overall performance of the resulting geopolymer foam concrete. DETAILED DESCRIPTION

[0027] In order to enable those skilled in the art to better understand the technical solutions and technical effects of the present invention, several embodiments are provided below. Obviously, what is described below is only an embodiment and does not limit the protection scope of the present invention.

[0028] The performance indicators of the raw materials used in each embodiment of the present invention are as follows:

[0029] The specific surface area of ​​steel slag powder is 417m 2 / kg; the fly ash is secondary fly ash, with a specific surface area of ​​421m 2 / kg; the mineral powder is S95 grade, with a specific surface area of ​​484m 2 / kg; the foaming agent is sodium dodecyl sulfate, which is a white powder; the foam stabilizer is hydroxypropyl methylcellulose, which is a white powder; the asphalt content in the cationic emulsified asphalt is 55%, and the demulsification time is 5 hours; the initial modulus of the sodium silicate solution is 3.29, wherein the mass ratio of SiO2 to Na2O is 3.2, and the solid content is 39.8%; the sodium hydroxide solution is a solution with a concentration of 14M prepared by dissolving sodium hydroxide particles with a purity greater than 99% in water.

[0030] Example 1

[0031] An emulsified asphalt modified high-strength thermal insulation geopolymer foam concrete is prepared by the following method:

[0032] 1) By weight, 100 parts of sodium silicate solution and 100 parts of sodium hydroxide solution were stirred and mixed uniformly, and then allowed to stand at room temperature for 24 hours to obtain solution A;

[0033] 2) By weight, 300 parts of slag powder, 100 parts of steel slag powder and 100 parts of fly ash were stirred and mixed uniformly to obtain a mixture B;

[0034] 3) Pour solution A and 250 parts of water into mixed material B by weight, stir and mix evenly to obtain geopolymer slurry;

[0035] 4) By weight, 0.2 parts of a foaming agent, 0.8 parts of a cationic emulsified asphalt and 10 parts of water are stirred and mixed uniformly to obtain an emulsified asphalt modified foaming agent;

[0036] 5) injecting compressed air into the emulsified asphalt modified foaming agent to mix and generate foam, then adding the foam into the geopolymer slurry and stirring and mixing evenly to obtain slurry C;

[0037] 6) Pour slurry C into a mold for curing, and after solidification, obtain emulsified asphalt modified high-strength thermal insulation geopolymer foam concrete.

[0038] Example 2

[0039] An emulsified asphalt modified high-strength thermal insulation geopolymer foam concrete is prepared by the following method:

[0040] 1) By weight, 100 parts of sodium silicate solution and 100 parts of sodium hydroxide solution were stirred and mixed uniformly, and then allowed to stand at room temperature for 24 hours to obtain solution A;

[0041] 2) By weight, 200 parts of slag powder, 200 parts of steel slag powder and 100 parts of fly ash are stirred and mixed uniformly to obtain a mixture B;

[0042] 3) Pour solution A and 250 parts of water into mixed material B by weight, stir and mix evenly to obtain geopolymer slurry;

[0043] 4) By weight, 0.2 parts of a foaming agent, 1.6 parts of cationic emulsified asphalt and 10 parts of water were stirred and mixed uniformly to obtain an emulsified asphalt modified foaming agent;

[0044] 5) injecting compressed air into the emulsified asphalt modified foaming agent to mix and generate foam, then adding the foam into the geopolymer slurry and stirring and mixing evenly to obtain slurry C;

[0045] 6) Pour slurry C into a mold for curing, and after solidification, obtain emulsified asphalt modified high-strength thermal insulation geopolymer foam concrete.

[0046] Example 3

[0047] An emulsified asphalt modified high-strength thermal insulation geopolymer foam concrete is prepared by the following method:

[0048] 1) By weight, 100 parts of sodium silicate solution and 100 parts of sodium hydroxide solution were stirred and mixed uniformly, and then allowed to stand at room temperature for 24 hours to obtain solution A;

[0049] 2) By weight, 200 parts of slag powder, 100 parts of steel slag powder and 200 parts of fly ash are stirred and mixed uniformly to obtain a mixture B;

[0050] 3) Pour solution A and 250 parts of water into mixed material B by weight, stir and mix evenly to obtain geopolymer slurry;

[0051] 4) By weight, 0.2 parts of a foaming agent, 0.8 parts of a cationic emulsified asphalt and 10 parts of water are stirred and mixed uniformly to obtain an emulsified asphalt modified foaming agent;

[0052] 5) injecting compressed air into the emulsified asphalt modified foaming agent to mix and generate foam, then adding the foam into the geopolymer slurry and stirring and mixing evenly to obtain slurry C;

[0053] 6) Pour slurry C into a mold for curing, and after solidification, obtain emulsified asphalt modified high-strength thermal insulation geopolymer foam concrete.

[0054] Example 4

[0055] An emulsified asphalt modified high-strength thermal insulation geopolymer foam concrete is prepared by the following method:

[0056] 1) By weight, 100 parts of sodium silicate solution and 100 parts of sodium hydroxide solution were stirred and mixed uniformly, and then allowed to stand at room temperature for 24 hours to obtain solution A;

[0057] 2) By weight, 300 parts of slag powder, 100 parts of steel slag powder and 100 parts of fly ash were stirred and mixed uniformly to obtain a mixture B;

[0058] 3) Pour solution A and 250 parts of water into mixed material B by weight, stir and mix evenly to obtain geopolymer slurry;

[0059] 4) By weight, 0.2 parts of a foaming agent, 0.8 parts of a cationic emulsified asphalt, 1 part of a foam stabilizer and 10 parts of water are stirred and mixed uniformly to obtain an emulsified asphalt modified foaming agent;

[0060] 5) injecting compressed air into the emulsified asphalt modified foaming agent to mix and generate foam, then adding the foam into the geopolymer slurry and stirring and mixing evenly to obtain slurry C;

[0061] 6) Pour slurry C into a mold for curing, and after solidification, obtain emulsified asphalt modified high-strength thermal insulation geopolymer foam concrete.

[0062] Comparative Example 1

[0063] The difference between this comparative example and Example 1 is that: no slag powder is added in this comparative example; the total amount of slag powder, steel slag powder and fly ash remains unchanged. Specifically, the emulsified asphalt modified geopolymer foamed concrete in this comparative example is prepared by the following method:

[0064] 1) By weight, 100 parts of sodium silicate solution and 100 parts of sodium hydroxide solution were stirred and mixed uniformly, and then allowed to stand at room temperature for 24 hours to obtain solution A;

[0065] 2) By weight, 250 parts of steel slag powder and 250 parts of fly ash were stirred and mixed uniformly to obtain a mixture B;

[0066] 3) Pour solution A and 250 parts of water into mixed material B by weight, stir and mix evenly to obtain geopolymer slurry;

[0067] 4) By weight, 0.2 parts of a foaming agent, 0.8 parts of a cationic emulsified asphalt and 10 parts of water are stirred and mixed uniformly to obtain an emulsified asphalt modified foaming agent;

[0068] 5) injecting compressed air into the emulsified asphalt modified foaming agent to mix and generate foam, then adding the foam into the geopolymer slurry and stirring and mixing evenly to obtain slurry C;

[0069] 6) Pour slurry C into a mold for curing and solidification to obtain emulsified asphalt modified geopolymer foam concrete.

[0070] Comparative Example 2

[0071] The difference between this comparative example and Example 2 is that this comparative example does not add emulsified asphalt to prepare the modified foaming agent, but directly dissolves the foaming agent in water for foaming. Specifically, this comparative example prepares geopolymer foam concrete by the following method:

[0072] 1) By weight, 100 parts of sodium silicate solution and 100 parts of sodium hydroxide solution were stirred and mixed uniformly, and then allowed to stand at room temperature for 24 hours to obtain solution A;

[0073] 2) By weight, 200 parts of slag powder, 200 parts of steel slag powder and 100 parts of fly ash are stirred and mixed uniformly to obtain a mixture B;

[0074] 3) Pour solution A and 250 parts of water into mixed material B by weight, stir and mix evenly to obtain geopolymer slurry;

[0075] 4) By weight, 0.2 parts of a foaming agent and 10 parts of water are stirred and mixed uniformly to obtain a foaming agent;

[0076] 5) injecting compressed air into the foaming agent to mix and generate foam, then adding the foam into the geopolymer slurry and stirring and mixing evenly to obtain slurry C;

[0077] 6) Pour slurry C into a mold for curing and solidification to obtain geopolymer foam concrete.

[0078] Comparative Example 3

[0079] The difference between this comparative example and Example 3 is that: in this comparative example, the emulsified asphalt and the foaming agent are not mixed to prepare the modified foam, but the emulsified asphalt is directly mixed with the geopolymer slurry, and then the foam is added to prepare the foamed concrete. Specifically, the emulsified asphalt modified geopolymer foamed concrete is prepared by the following method in this comparative example:

[0080] 1) By weight, 100 parts of sodium silicate solution and 100 parts of sodium hydroxide solution were stirred and mixed uniformly, and then allowed to stand at room temperature for 24 hours to obtain solution A;

[0081] 2) By weight, 200 parts of slag powder, 100 parts of steel slag powder and 200 parts of fly ash are stirred and mixed uniformly to obtain a mixture B;

[0082] 3) Pour solution A and 250 parts of water into mixture B by weight, stir and mix until uniform, then add 0.8 parts of cationic emulsified asphalt, continue to stir and mix until uniform, and obtain geopolymer slurry;

[0083] 4) By weight, 0.2 parts of a foaming agent and 10 parts of water are stirred and mixed uniformly to obtain a foaming agent;

[0084] 5) injecting compressed air into the emulsified asphalt modified foaming agent to mix and generate foam, then adding the foam into the geopolymer slurry and stirring and mixing evenly to obtain slurry C;

[0085] 6) Pour slurry C into a mold for curing, and after solidification, obtain emulsified asphalt modified high-strength thermal insulation geopolymer foam concrete.

[0086] Referring to JG / T 266-2011 "Foamed Concrete", the 28d compressive strength, dry density, water absorption, thermal conductivity and other properties of the geopolymer foamed concrete in Examples 1-3 and Comparative Examples 1-3 were tested. The test results are shown in Table 1.

[0087] According to the experimental results in Table 1, by comparing the performance results of Example 1 and Comparative Example 1, it can be found that although the absence of slag has little effect on the dry density, water absorption and thermal conductivity of the emulsified asphalt modified geopolymer foam concrete, its 28d compressive strength decreases by 54.8%. This shows that the addition of slag can significantly improve the compressive strength of the emulsified asphalt modified geopolymer foam concrete, thereby solving the problem of decreased strength of the foam concrete caused by excessive slag addition.

[0088] By comparing the performance results of Example 2 and Comparative Example 2, it can be found that when the emulsified asphalt is removed, the water absorption and thermal conductivity of the geopolymer foam concrete are significantly increased, indicating that the addition of emulsified asphalt can increase the waterproof and thermal insulation properties of the geopolymer foam concrete. In addition, compared with Example 2, the dry density of the foamed concrete in Comparative Example 2 increased by 24.3%, indicating that the prefabricated foam prepared using emulsified asphalt has better strength and stability than ordinary prefabricated foam, thereby increasing the porosity of the foamed concrete and reducing the dry density.

[0089] By comparing the performance results of Example 3 and Comparative Example 3, it can be found that compared with the modified foam prepared by mixing emulsified asphalt with a foaming agent, the dry density, water absorption rate and thermal conductivity of the geopolymer foam concrete prepared by directly adding emulsified asphalt to the geopolymer slurry increase, and the 28d compressive strength decreases. It shows that the dispersibility of emulsified asphalt in the geopolymer slurry is poor, the emulsified asphalt directly added to the geopolymer slurry cannot be evenly distributed in the geopolymer foam concrete, and the emulsified asphalt cannot play a role in enhancing the foam, resulting in a decrease in the porosity, thermal insulation performance and 28d compressive strength of the foam concrete. On the contrary, the geopolymer foam concrete prepared by using emulsified asphalt modified foam has a lower density and more excellent thermal insulation and waterproof performance, indicating that the process adopted by the present invention can effectively improve the uniformity of the distribution of emulsified asphalt in the foam concrete.

[0090] By comparing the performance results of Example 1 and Example 4, it can be found that compared with the emulsified asphalt modified geopolymer foam concrete without adding a foam stabilizer, after adding the foam stabilizer, the dry density of the geopolymer foam concrete decreased by 10%, but the compressive strength did not change significantly, and the water absorption rate and thermal conductivity decreased significantly. This shows that the addition of the foam stabilizer further enhances the stability of the foam and optimizes the pore structure, thereby enhancing the mechanical properties and waterproof and thermal insulation properties of the geopolymer foam concrete.

[0091] According to the performance comparison results of the above comparative examples and embodiments, the emulsified asphalt modified high-strength thermal insulation geopolymer foam concrete prepared by the present invention shows better effects in mechanical properties, lightweight properties and thermal insulation properties. In addition, this material is also a low-carbon green high-performance building material with good application prospects and engineering value.

[0092] Table 1

[0093] Sample No. <![CDATA[Dry density (kg / m 3 )]]> 28d compressive strength (MPa) Water absorption (%) Thermal conductivity (W / m·k) Example 1 1023 16.6 16.1 0.314 Example 2 1064 13.1 15.8 0.322 Example 3 954 14.8 13.2 0.255 Example 4 921 16.2 12.8 0.271 Comparative Example 1 1054 9.1 17.2 0.331 Comparative Example 2 1186 13.2 23.4 0.463 Comparative Example 3 1123 12.5 18.6 0.382

[0094] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An emulsified asphalt modified high-strength thermal insulation geopolymer foam concrete, characterized in that: The foam obtained by emulsified asphalt modified foaming agent is mixed into geopolymer slurry, and is obtained by stirring, forming, curing, and solidification; the geopolymer slurry includes the following components by weight: 100-300 parts of slag powder, 100-200 parts of steel slag powder, 100-200 parts of fly ash, 100-150 parts of sodium silicate solution, 100-150 parts of sodium hydroxide solution, and 200-400 parts of water; The emulsified asphalt modified foaming agent comprises the following components by weight: 0.2-0.3 parts of foaming agent, 10-15 parts of water, and 0.8-2.7 parts of cationic emulsified asphalt.

2. The emulsified asphalt modified high-strength thermal insulation geopolymer foam concrete according to claim 1, characterized in that: The emulsified asphalt modified foaming agent also includes 0.6-1 parts of foam stabilizer by weight.

3. The emulsified asphalt modified high-strength thermal insulation geopolymer foam concrete according to claim 2, characterized in that: In parts by weight, the foam stabilizer is one or more of hydroxypropyl methylcellulose, polymethacrylamide, and carbon nanotubes.

4. The emulsified asphalt modified high-strength thermal insulation geopolymer foam concrete according to claim 1, characterized in that: The fineness of the slag powder, the steel slag powder and the fly ash are all greater than 400 meshes.

5. The emulsified asphalt modified high-strength thermal insulation geopolymer foam concrete according to claim 1, characterized in that: The asphalt content in the cationic emulsified asphalt is 50%-60%, and the demulsification time is greater than 4 hours; the foaming agent is one or more of sodium dodecyl sulfate, sodium methacrylic acid, and polymethacrylic acid.

6. The emulsified asphalt modified high-strength thermal insulation geopolymer foam concrete according to claim 1, characterized in that: The initial modulus of the sodium silicate solution is 3.3-3.5, wherein the mass ratio of SiO2 to Na2O is 3.25-3.35, and the solid content is greater than 30%.

7. The emulsified asphalt modified high-strength thermal insulation geopolymer foam concrete according to claim 1, characterized in that: The sodium hydroxide solution is a solution with a concentration of 12-14M prepared by dissolving sodium hydroxide particles with a purity greater than 99% in water.

8. A method for preparing the emulsified asphalt modified high-strength thermal insulation geopolymer foam concrete according to any one of claims 1 to 7, characterized in that: The following steps are involved: 1) stirring and mixing the sodium silicate solution and the sodium hydroxide solution uniformly, and then leaving the mixture at room temperature for 24 hours to obtain a solution A; 2) stirring and mixing the slag powder, the steel slag powder and the fly ash to obtain a mixture B; 3) pouring the solution A and 200-400 parts of the water into the mixture B, stirring and mixing evenly to obtain a geopolymer slurry; 4) stirring and mixing the foaming agent, the cationic emulsified asphalt and 10-15 parts of the water to obtain an emulsified asphalt modified foaming agent; 5) injecting compressed air into the emulsified asphalt modified foaming agent to mix and generate foam, then adding the foam into the geopolymer slurry and stirring and mixing to obtain slurry C; 6) The slurry C is poured into a mold for curing and solidification to obtain emulsified asphalt modified high-strength thermal insulation geopolymer foam concrete.

9. The method for preparing the emulsified asphalt modified high-strength thermal insulation geopolymer foam concrete according to claim 8, characterized in that: The stirring time in step 1) is not less than 1 hour; the stirring time in step 2) is not less than 2 minutes; the stirring time in step 3) is not less than 2 minutes; the stirring time in step 4) is not less than 1 hour.

10. The method for preparing the emulsified asphalt modified high-strength thermal insulation geopolymer foam concrete according to claim 8, characterized in that: The stirring speed in step 5) is 50-60 rpm, and the stirring time is 2-3 min.

Citation Information

Patent Citations

  • Emulsified asphalt cement stabilized macadam

    CN105198316A

  • A method for preparing an ultralightweight foamed concrete waterproof coating and the resulting ultralightweight foamed concrete with ultra-low water absorption.

    CN109761643B

  • Novel cement emulsified asphalt mortar as well as preparation method and application thereof

    CN116514489A

  • Lightweight aggregate geopolymer foam concrete and preparation method thereof

    CN117585949A

  • Foaming agent for civil construction as well as preparation method and use thereof

    CN101224957A